Manipulation with Raw Ceramic Chimney Pipes - Kellner, Tomas; Kyncl, Martin; Kyncl, Jiri; Koptis, Michal; Urban, Jan; Beranek, Libor; Kotoucek, Miroslav (Manufacturing Technology Journal, 2019)
The aim of the paper is to describe the design of the manipulation system for the raw ceramic chimney pipe raw blank to avoid deformation of the pipe during handling and to increase the productivity of the manufacturing process. The process of manufacturing of a ceramic chimney pipe begins with extrusion of the raw refractory material. The extruded semi-finished product is then processed and then transferred by hand to a kiln car on which it is dried and fired. It is this manipulation that heavily contributes in the deformation of the fired chimney pipes. Due to the low stiffness of the raw ceramic chimney pipe, deformation occurs by manual handling. In order to avoid these deformations, it is necessary to design a suitable concept and construction solution of the manipulation system. Due to the nature of the chimney pipe, the automation of manipulation is rather difficult. The pipe is very soft in the raw state, its surface is rough, wet and greasy. This paper deals with the design of an optimal solution for the manipulation of ceramic chimney pipes, which will prevent the chimney pipe from deforming, negatively affecting its quality and making it possible to increase the productivity of ceramic chimney pipes production.
Keywords: Manipulation with Pipes; Refractory; Ceramic Chimney Pipe; Automation; Gripper Design